Role and mechanism of circ-PRKCI in hepatocellular carcinoma - Qi, Su-Xia (World J Gastroenterol, 2019)
BACKGROUND: The circular RNA circ-PRKCI is an endogenous non-coding RNA that forms a covalently closed ring after reverse splicing, which plays a key role in the occurrence and development of multiple digestive system tumors. AIM: To investigate the role and mechanism of circ-PRKCI in the occurrence and development of hepatocellular carcinoma (HCC). METHODS: This study used real-time polymerase chain reaction to detect the expression of circ-PRKCI in tumor tissues, tumor adjacent tissues, and blood in patients with HCC and other digestive system tumor cells. A series of functional tests were performed to explore whether circ-PRKCI affects the growth of HCC cells and what is its mechanism in HCC. Meanwhile, fluorescence in situ hybridization was used to detect the subcellular localization of circ-PRKCI. Survival analysis was performed to predict the correlation between circ-PRKCI and the prognosis of HCC. Chi-square test and t-test were performed for statistical analyses. RESULTS: The level of circ-PRKCI was significantly higher in HCC tissues than in tumor adjacent tissues, and in HCC cell lines than in cells lines of esophageal, liver, stomach, and colon cancers. A series of functional tests showed that circ-PRKCI substantially inhibited cell apoptosis and promoted cell invasion. It was found that circ-PRKCI can act as the sponge of miRNA-545 to reduce the expression of AKT3 protein. Moreover, the result of survival analysis showed that circ-PRKCI target gene E2F7 can reduce liver cancer patients’ survival rate. And clinical data suggested that the distribution of circ-PRKCI rose with the depth of invasion, lymph node metastasis, distant metastasis, and TNM stage, indicating that circ-PRKCI may affect the survival and prognosis of patients with HCC by regulating E2E7. CONCLUSION: This study explores the role and mechanism of circ-PRKCI in HCC, which provides a new research direction and theoretical basis for the treatment of HCC.